Improvement Butt Weld of SSM aluminum alloys by Semi-solid State Joining - บิลหร่อหีม, ภัสพล; เมืองจันทร์บุรี, ประภาศ; เต๊ะยอ, มูหามัด (Princess of Naradhiwas University Journal, 2019)
This applied research aimed to improve butt weld of SSM aluminum alloy by using semisolid state joining. Physical properties were studied, including macro and micro structures, as well as mechanical properties of SSM 356 weld by semisolid state. Butt-joint of SSM356 was heated by induction heater. During welding, temperature was controlled in the range of 580-590ºC. Samples were welded by portable drill tip stirring of 4 mm diameter. The stirring rate and welding speed were 1,750 rpm. and 75 mm./min, respectively. The elded specimens had 3 different conditions. Firstly, the 1st and 2nd conditions were welded under normal atmosphere in order to investigate which direction of drill could give the best mechanical properties of weld joints, clockwise and counter clockwise. Result showed that the clockwise direction provided slightly higher physical properties, macro/microstructure properties, and mechanical properties. Therefore the 3rd ondition was welded under sledding gas (nitrogen gas) with the same welding parameter of clockwise irection. The gas flow rate and gas temperature were 5 L/min and 300ºC, respectively. Then, the results withprevious experiment were compared under normal atmospheres. The results showed that welded sample under nitrogen gas (Tensile strength 121.7 MPa and Hardness 63.9 Hv(0.1)) gave better mechanical properties compared to the experiment under normal atmosphere (tensile strength 111.2 MPa and Hardness 63.2 Hv(0.1)).